Comprehensive management of patients with pelvis organ prolapse and metabolic syndrome - Irina A. Lapina; Yulia E. Dobrokhotova; Vladislav V. Taranov; Tatiana G. Chirvon; Polina Volkova; Anastasia A. Malakhova (IP Berlin A.V., 2021)
Background. Genital prolapse (GP) and stress urinary incontinence (SUI) are characterized by a failure of connective tissue skeleton of the pelvic floor structures, and there are many risk factors in their pathogenesis. Metabolic syndrome (MS), which includes obesity and abnormalities in the lipid and carbohydrate profile, contributes to the initiation of pelvic organ prolapse (POP) due to increased intra-abdominal pressure and the presence of comorbidities. Endothelial dysfunction associated with MS aggravates the existing metabolic disorders, resulting in the formation of a vicious circle and an increase in the likelihood of recurrence of genital prolapse symptoms and НМ during tension in the postoperative period. Aim. The search for rational algorithms for the comprehensive management of patients with POP and MS. Materials and methods. A comparative analysis of effectiveness of treatment with the use of surgical method or drugs which affect the metabolic profile in patients with GP and SUI was carried out. Results. Drugs which contribute the restoration of lipid and carbohydrate profiles, and microcirculatory vasculature normalization, attenuate negative effects of MS components on the integrity of pelvic floor structures. Comprehensive management of patients with POP and MS with surgical correction of GP and SUI, as well as the use of drugs affecting metabolism, is highly effective and predictive in regard to POP severity and the risk of recurrence of clinical symptoms in the postoperative period. Conclusion. Adequate restoration of the endothelial layer in patients with pelvic floor muscle incompetence and endothelial dysfunction reduces the likelihood of developing mesh-associated complications after the surgical stage of treatment.